Mathematical formulas for industrial and mechanical engineering - Kadry, Seifedine, 1977- (Amsterdam : Elsevier, 2014)
Annotation Mathematical Formulas For Industrial and Mechanical Engineering serves the needs of students and teachers as well as professional workers in engineering who use mathematics. The contents and size make it especially convenient and portable. The widespread availability and low price of scientific calculators have greatly reduced the need for many numerical tables that make most handbooks bulky. However, most calculators do not give integrals, derivatives, series and other mathematical formulas and figures that are often needed. Accordingly, this book contains that information in an easy way to access in addition to illustrative examples that make formulas clearer. Students and professionals alike will find this book a valuable supplement to standard textbooks, a source for review, and a handy reference for many years. Covers mathematics formulas needed for Industrial and Mechanical EngineeringQuick and easy to use reference and studyIncludes practical examples and figures to help quickly understand concepts.
Keywords: Industrial engineering -- Mathematics; Mechanical engineering -- Mathematics; Mathematics -- Formulae